2018
DOI: 10.1186/s12870-018-1534-8
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of transcripts and splice isoforms in red clover (Trifolium pratense L.) by single-molecule long-read sequencing

Abstract: BackgroundRed clover (Trifolium pratense L.) is an important cool-season legume plant, which is the most widely planted forage legume after alfalfa. Although a draft genome sequence was published already, the sequences and completed structure of mRNA transcripts remain unclear, which limit further explore on red clover.ResultsIn this study, the red clover transcriptome was sequenced using single-molecule long-read sequencing to identify full-length splice isoforms, and 29,730 novel isoforms from known genes an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
53
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(64 citation statements)
references
References 33 publications
11
53
0
Order By: Relevance
“…The human transcriptome was revealed to be much more complex than previously expected owing to the application of TGS technology, which identified an array of novel isoforms that had not yet been annotated [9]. Similar findings were reported in some other species such as pigs [39], rabbits [26], switchgrass [13], red clover [30], and so forth. In the present study, we identified 2405 novel genic loci from unannotated regions and 11,623 new isoforms from various exons in the draft genome based on SMRT data, suggestive of a more complex transcriptome of A. apis .…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The human transcriptome was revealed to be much more complex than previously expected owing to the application of TGS technology, which identified an array of novel isoforms that had not yet been annotated [9]. Similar findings were reported in some other species such as pigs [39], rabbits [26], switchgrass [13], red clover [30], and so forth. In the present study, we identified 2405 novel genic loci from unannotated regions and 11,623 new isoforms from various exons in the draft genome based on SMRT data, suggestive of a more complex transcriptome of A. apis .…”
Section: Discussionsupporting
confidence: 52%
“…TFs are key components involved in the transcriptional regulatory system in various animals, plants, and insects [12,30]. A total of 253 members from 17 TF families were identified from our transcript datasets.…”
Section: Resultsmentioning
confidence: 99%
“…After comparing the identified PASs to the Ensembl reference annotation, we not only found that a large number of PASs are located in the intergenic regions, but also confirmed the existence of partial misannotated genes, which reflected the incompleteness of the current annotation. Single-molecule long-read sequencing technology is sufficient for the complete assembly of most known microbial genomes and has been applied to research studies of many species by now [26,27,30]. With the PacBio SMRT sequencing technology employment to whole-transcriptome profiling in rabbit, Chen et al obtained 36,186 high-confidence transcripts and detected 24,797 alternative splicing (AS) and 11,184 APA events, indicating a significant improvement in the current annotation of the rabbit [26].…”
Section: (C)mentioning
confidence: 99%
“…Especially, the Iso-seq library built with the oligo(dT) primer ensures the integrity of 3′ terminal. So far, the PacBio protocol Iso-Seq ™ has been successfully applied to characterize the posttranscriptional APA events in various eukaryotes [26][27][28][29][30]. Our study used the PacBio dataset to annotate PASs of pigs and analyzed differential usages and functions of APA genes under the regulation of miRNAs and RBPs between fast and slow muscles.…”
Section: Introductionmentioning
confidence: 99%
“…One important reason behind the lack of functional perspective in splicingdedicated bioinformatics tools is the inability of RNAseq to correctly capture isoform expression 51 . Recently, third generation sequencing technologies have demonstrated their power in detecting full-length transcript [52][53][54][55][56] and identifying expressed isoforms. Options for quantification are found in the combination with short-reads 55 or the utilization of the newest high throughput instruments.…”
mentioning
confidence: 99%